The Effectiveness of Audio Repetition in Enhancing Listening Comprehension - Marzona, Yessy (Fakultas Sastra Universitas Ekasakti, 2025)
Listening comprehension is a fundamental skill in language acquisition, yet it remains one of the most challenging aspects for English as a Foreign Language (EFL) learners. One of the strategies proposed to support listening development is audio repetition—allowing learners to listen to audio materials more than once to aid in understanding and retention. This reserach aims to examine the effectiveness of audio repetition in enhancing students’ listening comprehension skills. Conducted with a group of 40 eleventh-grade EFL students at a senior high school in Indonesia, the research employed a quasi-experimental design. The participants were divided into two groups: the experimental group received listening instruction with audio repetition (each audio was played twice), while the control group listened to the same materials only once. A pre-test and post-test were administered to both groups to measure improvement in listening comprehension. The results indicated a significant increase in the post-test scores of the experimental group compared to the control group. Students exposed to repeated audio demonstrated better understanding of main ideas, specific details, and contextual meanings. Furthermore, the repetition helped reduce anxiety and improved students’ confidence during listening tasks. Interviews and questionnaires supported the quantitative findings, showing positive student perceptions of audio repetition as a helpful tool in learning listening. The findings suggest that incorporating audio repetition into classroom instruction can be an effective strategy to improve EFL students' listening skills, especially in contexts where exposure to English is limited. Teachers are encouraged to utilize this method, particularly at the intermediate level, to scaffold students’ comprehension and promote more active engagement with listening texts. Future studies may explore the optimal number of repetitions and its impact across different proficiency levels.